Effect of Hepatic Impairment on the Pharmacokinetics of Baicalin in Rats: Critical Roles of Gut Microbiota and Hepatic Transporters - Ping Li; Yihua Tian; Hong Wang; Yuting Ji; Huiying Zeng; Shengman Zhang; Xiuli Gao; Xiaoyan Chen (Pharmaceutics)
Background: Baicalin (BG) has been used in the treatment of many diseases. However, the effect of hepatic insufficiency on its pharmacokinetics has not been reported, and there is a lack of clinical guidance for the use of BG in patients with hepatic impairment. Methods: Carbon tetrachloride (CCl4)-induced rat models were used to simulate hepatic failure patients to assess the effect of hepatic impairment on the pharmacokinetics and distribution of BG. In vitro metabolism and transporter studies were employed to elucidate the potential mechanisms. Results: After intragastric administration of 10 mg/kg of BG, the peak plasma concentration and exposure (AUC0–t) of BG decreased by 64.6% and 52.6%, respectively, in CCl4-induced rats. After intravenous administration, the AUC0–t decreased by 73.6%, and unlike in the control group, the second absorption peak of BG was not obvious in the concentration–time curve of CCl4-induced rats. The cumulative excretion of BG in the feces increased, but that in the bile decreased. In vivo data indicated that the absorption and enterohepatic circulation of BG were affected. In vitro studies found that the hydrolysis of BG to the aglycone baicalein decreased significantly in the intestinal tissues and contents of the CCl4-induced rats. And BG was identified as a substrate for multiple efflux and uptake transporters, such as breast cancer resistance protein (BCRP) and multidrug resistance-associated proteins (MRPs), organic anion transporting polypeptides (OATP1B1, 1B3, 2B1), and organic anion transporters (OATs). The bile acids accumulated by liver injury inhibited the uptake of BG by OATPs, especially that by OATP2B1. Conclusions: Hepatic impairment reduced BG hydrolysis by intestinal microflora and inhibited its transporter-mediated biliary excretion, which synergistically led to the attenuation of the enterohepatic circulation of BG, which altered its pharmacokinetics.